KEPAILITAN PT. TOZI SENTOSA AKIBAT PANDEMI COVID-19 - Makmur Makmur (Jurnal Hukum Mimbar Justitia, 2022)
Activity restrictions due to the Covid-19 pandemic have affected economic activity nationally. Restrictions on community activities affect business activities which then have an impact on the economy. The economic impact during the covid period will only be covered if the crisis can be ended before causing mass business bankruptcy. Indonesia's global economy is experiencing uncertainty and is leading to an economic recession due to the Covid-19 pandemic. However, currently there are several business activities that have been declared bankrupt due to the Covid19 pandemic. One of the companies that experienced bankruptcy during the Covid-19 pandemic was the retail company Centro Department Store.Â Keywords: Bankruptcy; Business; Economy; Law; Pandemic.